Treatment with PCSK9 Inhibitor Evolocumab Improves Vascular Oxidative Stress and Arterial Stiffness in Hypercholesterolemic Patients with High Cardiovascular Risk - Alessia Silla; Federica Fogacci; Angela Punzo; Silvana Hrelia; Patrizia Simoni; Cristiana Caliceti; Arrigo F. G. Cicero (MDPI AG, 2023)
Atherosclerosis and atherosclerotic-related cardiovascular diseases (ASCVD) are characterized by high serum levels of low-density lipoprotein cholesterol (LDL-C) that can promote the generation of reactive oxygen species (ROS). To answer the need for better LDL-C control in individuals at high and very high risk for CVD, a new injectable innovative family of lipid-lowering (LL) monoclonal antibodies against the protein convertase subtilisin/kexin type 9 (PCSK9) has been approved. However, the effect of these drugs on vascular function, such as ROS generation and arterial stiffness, has not already been extensively described. In this report, we present data from 18 males with high to very high CV risk undergoing LL treatment (LLT) with either statin and ezetimibe or ezetimibe monotherapy, who experienced, after a 2-month treatment with Evolocumab, a significant improvement in blood pressure (BP)-adjusted carotid-femoral pulse wave velocity (cfPWV) (p-value = 0.0005 in the whole cohort, p-value = 0.0046 in the sub-cohort undergoing background LLT with statin and ezetimibe, p-value = 0.015 in the sub-cohort undergoing background LLT with ezetimibe monotherapy), which was significantly associated with a decrease in freshly isolated leukocytes (PBMCS)-derived H2O2 production (p-value = 0.004, p-value = 0.02 and p-value = 0.05, respectively, in the whole cohort, in the statin + ezetimibe sub-cohort, and the ezetimibe sub-cohort). Our observations support the role of systemic oxidative stress in atherosclerosis and give a further rationale for using Evolocumab also for its effect in vascular disorders linked to oxidative processes.